2016
DOI: 10.3390/nu8090569
|View full text |Cite
|
Sign up to set email alerts
|

Current Hypothesis for the Relationship between Dietary Rice Bran Intake, the Intestinal Microbiota and Colorectal Cancer Prevention

Abstract: Globally, colorectal cancer (CRC) is the third most common form of cancer. The development of effective chemopreventive strategies to reduce CRC incidence is therefore of paramount importance. Over the past decade, research has indicated the potential of rice bran, a byproduct of rice milling, in CRC chemoprevention. This was recently suggested to be partly attributable to modification in the composition of intestinal microbiota when rice bran was ingested. Indeed, previous studies have reported changes in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 84 publications
2
18
0
Order By: Relevance
“…The increased occurrence of colorectal cancer in several countries may reflect the increase in risk factors of this cancer, such as unhealthy diet (Center, Jemal, Smith, & Ward, ). In addition, intestinal microbial dysbiosis, the change in population size of certain bacterial species, also plays an important role in colorectal carcinogenesis (So, Law, Law, & Chan, ). Some researchers have indicated that modulation of gut microbiota positively affects the interaction between microbiota and immune system and may be beneficial in suppressing colorectal carcinogenesis (Ambalam, Raman, Purama, & Doble, ).…”
Section: Introductionmentioning
confidence: 99%
“…The increased occurrence of colorectal cancer in several countries may reflect the increase in risk factors of this cancer, such as unhealthy diet (Center, Jemal, Smith, & Ward, ). In addition, intestinal microbial dysbiosis, the change in population size of certain bacterial species, also plays an important role in colorectal carcinogenesis (So, Law, Law, & Chan, ). Some researchers have indicated that modulation of gut microbiota positively affects the interaction between microbiota and immune system and may be beneficial in suppressing colorectal carcinogenesis (Ambalam, Raman, Purama, & Doble, ).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the search yielded 498 articles, and 320 remained for further evaluation after 178 duplicated articles were excluded. Of the 23 full‐text reports remaining after title and abstract screening, four studies (Denova‐Gutierrez, Hernandez‐Ramirez, & Lopez‐Carrillo, ; Karagulle, Fidan, Kavgaci, & Ozdemir, ; Terry, Lagergren, Ye, Wolk, & Nyren, ; Wang et al., ) without available OR and 95% CI were ruled out, and another eight studies (Fraser, ; Gil, Ortega, & Maldonado, ; Jansen et al., ; Lafiandra, Riccardi, & Shewry, ; McCullough et al., ; Shamberger, Tytko, & Willis, ; So, Law, Law, Chan, & Chair, ; Vanamala, Massey, Pinnamaneni, Reddivari, & Reardon, ) were not included because they did not investigate cereal or grain consumption and GC risk. After this review, 11 observational studies evaluating the risk of GC remained for the analysis (Buckland et al., ; Chatenoud et al., ; Chen et al., ; De Stefani et al., ; Kasum, Jacobs, Nicodemus, & Folsom, ; Lissowska et al., ; Lucenteforte et al., ; RamĂłn, Serra, CerdĂł, & OromĂ­, ; Wang et al., ; Ward, ; Zhang et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Given that dietary rice bran intake has been previously shown to promote beneficial stool microbial communities, such as native gut probiotics in mice 23, 62 , pigs 21,22,29 and adults 25,63,64 , we first evaluated significant genus level taxa differences between rice bran and control fed infants at 8 months and 12 months of age from both countries. In Nicaragua, Lactobacillus, Lachnospiraceae, Bifidobacterium, Ruminococcaceae and Veillonella were identified as responsive following rice bran consumption compared to an age and control matched group.…”
Section: Discussionmentioning
confidence: 99%